2015
DOI: 10.1098/rsbl.2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Critically endangered western gray whales migrate to the eastern North Pacific

Abstract: Western North Pacific gray whales (WGWs), once considered extinct, are critically endangered with unknown migratory routes and reproductive areas. We attached satellite-monitored tags to seven WGWs on their primary feeding ground off Sakhalin Island, Russia, three of which subsequently migrated to regions occupied by non-endangered eastern gray whales (EGWs). A female with the longest-lasting tag visited all three major EGW reproductive areas off Baja California, Mexico, before returning to Sakhalin Island the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 14 publications
2
65
0
2
Order By: Relevance
“…Individual tracks can also provide significant information with conservation implications. For example, the track of a single grey whale (Eschrichtius robustus) tagged within the feeding grounds of the critically endangered western stock off Sakhalin Island, Russia, and migrating to the breeding lagoons of the eastern stock in Baja California, Mexico, questioned whether these two stocks were indeed distinct (Mate et al 2015). This individual whale also broke the world record (previously held by a humpback whale) for the longest known mammalian migration at 22,511 km.…”
Section: Fig 2 Examples Of Tracking Studies Using Various Sample Simentioning
confidence: 99%
“…Individual tracks can also provide significant information with conservation implications. For example, the track of a single grey whale (Eschrichtius robustus) tagged within the feeding grounds of the critically endangered western stock off Sakhalin Island, Russia, and migrating to the breeding lagoons of the eastern stock in Baja California, Mexico, questioned whether these two stocks were indeed distinct (Mate et al 2015). This individual whale also broke the world record (previously held by a humpback whale) for the longest known mammalian migration at 22,511 km.…”
Section: Fig 2 Examples Of Tracking Studies Using Various Sample Simentioning
confidence: 99%
“…), although satellite data have shown that the western whales migrate to Mexico, where they may mix with individuals from the eastern population (Mate et al. ).…”
Section: Mediterranean Fin Whale Migration In Contextmentioning
confidence: 99%
“…Opportunistic feeding along their entire range from Baja California to Alaskan waters has been documented in eastern Pacific grey whales, as well as year-round presence in the northern Gulf of Alaska ). Comparatively less is known of the migration paths and winter grounds of the north-western Pacific Ocean grey whales along the east coast of Asia (Swartz et al 2006), although satellite data have shown that the western whales migrate to Mexico, where they may mix with individuals from the eastern population (Mate et al 2015).…”
Section: Mysticete Migration Revisitedmentioning
confidence: 99%
“…Apart from the rich benthic prey biomass (average of 35.2 and 18.5 g m −2 for amphipods and isopods, respectively; Fadeev 2011), the Piltun feeding area is of particular importance to nursing/weaning gray whale calves, probably due at least in part to the relatively sheltered and shallow nature of the area . The location or locations of this population's wintering grounds are not well understood, but the whales are clearly migratory; at least some of them migrate from Sakhalin to low-latitude areas along the Baja California Peninsula, Mexico, where early calf rearing and courtship activity occur (Urban et al 2013, Mate et al 2015, and others possibly migrate to historical wintering grounds in the South China Sea (Weller et al 2002). The whales return to the Piltun feeding area in the period from June to July and remain until November.…”
Section: Introductionmentioning
confidence: 99%